Brokering research with war-affected people: The tense relationship between opportunities and ethics. (March 2018) - Schiltz, Julie; Büscher, Karen
This article examines the roles of brokers in conducting research in a (post-)conflict context and uses this analysis as a lens to rethink reflexive ethics in humanitarian research. Drawing on fieldwork in Gulu, northern Uganda, the paper analyses the ambiguous position of brokers, and the complex social space in which they navigate. The paper outlines how brokers, in the pursuit of opportunities and in trying to meet expectations of other players, use strategies such as concealing information for researchers, or actively promoting the research project rather than merely facilitating it. It is further argued that research in northern Uganda may reproduce conceptions of war-affected people as vulnerable and of the war-affected context as problem-fraught and in need of intervention. The paper concludes by seeking ways to rethink a reflexive ethical stance in humanitarian research and encourages researchers to take the role of brokers and other stakeholders into account.